Biegły rewident jako audytor projektów unijnych - Piotrowska, Katarzyna (Chartered Auditor as a European Union Projects' Auditor, 2007)
Since few years the Polish economic entities have been using European Union funds to finance projects that are implemented by European Commission programmes. Expected benefits are very often receptive to danger of presenting an incorrect account of received funds. European Commission, to prevent such situations, has imposed an obligation to implement a financial audit on all participants. This audit should be carried out by authorized entities. In Poland such entities among other things are chartered auditors. That is why the main purpose of this article is to find an answer for the following question: what kind of tasks are set to chartered auditors who audit the European Union projects.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 261-268